Aplikasi Pengajuan Cuti dan Izin Karyawan PT Bumi Arasy Konsultanindo - Rizal, Ahmad; Fauzi, Muhamad Imam; Nurdin, Rachmat Septian; Juanda, Jejen; Nirmala, Endar; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Standard operating procedures for submitting leave and permits and unclear mechanisms for recording and checking data that have not been assisted by an information system. In making a web-based Application for Leave and Employee Permit Applications for PT. Bumi Arasy Consultant, it is made with HTML, PHP and also MySql procedures which will provide efficiency and effectiveness for the company in processing and storing data in an orderly manner so that it is easier to get the information that will be needed.The purpose of this article and writing is to study, analyze, design, compile and implement a web-based information system at PT. Bumi Arasy Consultant that will support internal business processes within the Human Resource Department (HRD) Division.The software that we will develop in making this application is using HTML or what we usually call Hypertext Markup Language, which is the most basic language for the web scripting process and is Client Side which allows displaying information in the form of text, graphics, and also for attaching between web interfaces. In addition, to store and process data, we will use a programming language with PHP and MySQL database.The result of the process of developing a leave application information system is a web-based application program that can provide an overview and faster for submitting leave and employee permits for PT. Bumi Throne Consultindo. The results of the application of this method will simplify the administrative process and also be more organized in making reports on leave and employee permits, as well as providing handling for storing archives in an adequate container.